Wages in urban Brazil: Evidence of regional segmentation or national markets - William D. Savedoff (Institute for Applied Economic Research (ipea), 2015)
In spite of Brazil's rapid pace of economic integration in recent decades, there remains substantial evidence of regional differences in wages. Numerous studies have also cited the impact of the country's form of economic development on various skill and occupational categories. On the other hand, macroeconomic models generally simplify labor market processes by assuming a single homogeneous national labor market. Are wages in Brazil, then, determined by isolated regional, occupational, or nationwide factors? This study develops an econometric model for decomposing annual, occupational and regional effects on wages and applies it to the Brazilian urban labor force to test whether annual wage changes are more similar among occupational or local categories. It shows that wages are affected both by local conditions and national occupational trends, and furthermore that the underlying patterns of regional and occupational wage differentials are remarkably stable.
Keywords: 330